2002
DOI: 10.1292/jvms.64.577
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Application to Live Horse for Diagnosis of Tendinitis

Abstract: ABSTRACT. Six live horses with various stages of acute to chronic superficial digital flexor (SDF) tendinitis were examined using magnetic resonance imaging (MRI). In each case, MRI findings were compared to the corresponding ultrasonographic (USD) and histologic findings, to establish the usefulness of MRI. In the acute cases, lesions characterized by hemorrhage were well defined as high sig nal intensity on MRI and hypoechoic regions on USD. Chronic tendon fibrosis was slightly hyperechoic and difficult to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
44
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 13 publications
13
44
2
5
Order By: Relevance
“…We used low field system in this study and found this new ligament. Our MRI findings about suspensory ligament, SDFT, DDFT and accessory ligament of DDFT were similar to previous researchers' findings in the horse [3,5,13,14,22].…”
Section: Discussionsupporting
confidence: 92%
“…We used low field system in this study and found this new ligament. Our MRI findings about suspensory ligament, SDFT, DDFT and accessory ligament of DDFT were similar to previous researchers' findings in the horse [3,5,13,14,22].…”
Section: Discussionsupporting
confidence: 92%
“…[10][11][12] In horses, MRI provides a promising alternative imaging modality to ultrasonography for the evaluation of pathological changes in tendons. 9 Acute tendon inju- ries, which are characterized by early cellular infiltration prior to fluid accumulation or hemorrhage, have increased signal intensities on T1-and T2-weighted images. 9 Acute tendon inju- ries, which are characterized by early cellular infiltration prior to fluid accumulation or hemorrhage, have increased signal intensities on T1-and T2-weighted images.…”
mentioning
confidence: 99%
“…Im Gehirn von Pferden wurden Läsionen mittels MRT abgebildet, die durch "nigropallidal encephalomalacia", eine der humanen Parkinson-Krankheit ähnliche Pferdeerkrankung, hervorgerufen wurden (Sanders et al 2001). An einem 2 Monate alten Fohlen wurde unter anderem mittels MRT die Ursache für eine Myeloencephalitis untersucht (Gray et al 2001 (Kasashima et al 2002). Untersuchungen über den Einfluss den Training in Tretmühlen auf die Morphologie des Os tarsi centrale und des Os tarsi tertium bei Vollblutpferden hat, wurden mittels Dichtemessung an MR-Bildern vorgenommen (Whitton et al 1999).…”
Section: J Fitz Und H Gerhardsunclassified